Scientific basis of thermal safety analysis of dry storage of spent nuclear fuel on zaporizhska NPP - Alyokhina, S.; Kostikov, A.; Koriahina, I. (Вопросы атомной науки и техники, 2020)
Now only one Dry Storage Facility of Spent Nuclear Fuel (DSFSNF) is operated in Ukraine. It is the facility on Zaporizhska NPP. Many different thermal investigations were done for ventilated containers of DSFSNF. In this study the generalization of scientific approaches to the thermal safety assessment are carried out. The multi-stage approach to the definition of thermal state of containers' group, single container, spent fuel assemblies and fuel rods was developed. Detailed thermal profiles of spent fuel assemblies inside storage container were calculated. With usage of multi-stage approach the thermal simulations of the influence of outer factors onto thermal state of containers was carried out. Results of thermal investigations were generalized and factors, which are influence on thermal state of containers, are detected. The method of spent nuclear fuel thermal state prediction and suggestion for improving the system of thermal monitoring were proposed.